Kindergarten in the role of a learning community - Metić Admir (Univerzitetska Misao, 2024)
The aim of this paper is to present and analyze kindergarten - a learning community, as well as how to learn successfully in kindergarten. The paper uses the method of content analysis of available scientific literature, and theoretical and empirical material. Kindergarten is a type of educational institution in which many social roles, identities, as well as other forms of behavior appear. It is more than an "ordinary place" where information is transmitted because in combination with other social institutions, it represents the entire social population, roles, and identities of society. Kindergarten, as an institution for the educational process of children, is a place of great hope. Kindergarten reveals a lot about the role and status we attribute to children, as well as about our views on democracy, social protection, and society in general. This is of great symbolic significance for the kindergarten. It is a confirmation of how we adults understand childhood and its connection with the state, economy, civil society, culture, and the private sector.